The Use of Vlogging as a Media in Online Class - Desnita Desnita; Lusi Marleni (Universitas Pahlawan Tuanku Tambusai, 2020)
This research aims to find out whether there is an effect on using Vlogging as a media towards the students’ speaking skill in online class, in academic year 2019/2020. This research is quasi-experimental research that carried out at Eleventh grade students of MA Muallimin Muhammadiyah Bangkinang. It involved 52 students of two classes, XI Agama Putri as experimental class and XI Agama Putra as control class. Each class consisted of 26 students. The experimental class was taught by using Vlogging as a media while control class was taught by using Voice Recording. The data were analyzed by using T-test formula. Based on the collecting data, it was obtained that t_(count )is 6 and t_(table )is 1,67 where α is 0,05. It showed that t_(count )higher than t_(table )(6 higher than 1,67), so that〖 H〗_0 is rejected and H_a is accepted. It means there is a significant difference in the students’ speaking skill between the students who were taught by using Vlogging and those who were taught by using Voice Recording. Based on the result findings, it can be concluded that the use of Vlogging in teaching speaking skill in online class is effective.